KESIAPSIAGAAN SEKOLAH SD NEGERI 2 SANDEN KABUPATEN BANTUL DALAM MENGHADAPI BENCANA ALAM GEMPABUMI - Rahady, Mayang Kusumaning; Kurniawan, Ficky Adi (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2023)
Disaster education is very important, especially for schools in disaster-prone areas. Schools should teach disaster education, especially about attitudes and actions that must be taken when a disaster occurs. SD Negeri 2 Sanden is one of the elementary schools that is vulnerable to earthquake disasters. This research uses a qualitative descriptive method with a case study approach. The results of the research show that (1) All respondents understand the potential threat of priority disasters at SD Negeri 2 Sanden, namely earthquakes (2) SD Negeri 2 Sanden does not yet have a written policy regarding preparedness for facing disasters. School policies only exist in disaster mitigation efforts such as integrating disaster material into the curriculum (3) Emergency response plans have been carried out by the school, including saving data on Google Drive and carrying out disaster simulations. (4) The school opens access to communication and disaster warning information from relevant stakeholders and agrees together on the tools used to convey danger signs. (5) The school has not yet formed a School Disaster Preparedness Team that can mobilize resources when an earthquake occurs at SD Negeri 2 Sanden.